Analisis Produksi Pupuk Organik Cair (POC) dari Limbah Kulit Bawang dan Air Cucian Beras - Dwidya Nuari; Queen Helen Br.Bukit; Sri Muthia Hasan; Tamim Hasyimi; Ade Fransisca; Yenni Lestari; Rismauly Septiana; Tirza Grace; Qamara Aulia; Alvian Maranalom; Elfayetti Elfayetti (Lembaga Pengembangan Kinerja Dosen, 2024)
Organic fertilizer is very important in efforts to improve soil fertility naturally and safely, in the broadest sense of being free from chemicals that are harmful to human health, therefore this organic fertilizer is very safe for consumption. This research was carried out in a housing complex on Jl. Tombak, Medan Tembung District, Medan City, North Sumatra. The research method used in this research is the experimental and observation method. The aim of this research is to determine the content of organic fertilizer made from mixed waste of onion skins and garlic skins with used rice water washing. And the results of the research that has been carried out show that the organic fertilizer that the researchers made failed due to several factors, such as perhaps there being onion skins that had rotted and should not be used and also the fermentation process time was too long, so it did not meet the required standards. Apart from that, when filtering to remove onion skin waste, the liquid fertilizer the researchers made smelled pungent and rotten.